Ice sheet velocity tracking by Sentinel-1 satellite images at Graham Coast Kyiv Peninsula - Kadurin, S.; Andrieieva, K. (Ukrainian Antarctic Journal, 2021)
The study of Antarctic glaciers and ice sheets velocity is one of the most discussed topics. Such high interest in this topic is primarily because the ice from the Antarctic glaciers, which gets to the ocean, significantly affects the ocean level and the global climate. Development of modern satellite technologies for Earth remote sensing made it possible to elaborate a number of methods for ice sheets’ displacements estimation and calculation of such displacements velocities. This work uses remote sensing data from the satellite system Copernicus Sentinel-1 to estimate the ice cover velocities in the Kyiv Peninsula in the time interval from December 2020 to March 2021. To this end, 10 radar images of the study area from early December to the end of March were used with an interval of 12–14 days. All selected images were analyzed in pairs to establish changes on the surface for the selected time interval. GRD-format images from Copernicus Sentinel-1 satellite, corrected for Earth’s ellipsoid shape, were used. Based on the offset tracking operation, we calculated the speeds of ice cover movements within the Kyiv Peninsula for each pair of images with approximately two weeks’ time difference. As a result, the speed of ice movements varies considerably and at the glacier mouth can reach 3.5–4 meters per day. Also, the rate of ice displacement in the glacier body changed over time. Thus, the highest ice velocities were in the glacier’s mouth. However, short-term time intervals of intensification were recorded for the rear and even the marginal parts of the glaciers in contact with the ice sheet. Thus, the lowest part of the glacier activating sequence leads to the upper part shifting. Notably, this increase in the displacement of ice cover was recorded in February, one of the warmest months in this part of Antarctica.